DEVELOPMENT OF STUDENT WORKSHEET IN NATURAL SCIENCE LEARNING BASED ON PREDICT-OBSERVE-EXPLAIN (POE) TO IMPROVE SCIENCE PROCESS SKILLS - Miftaqul Janah; Ekosari Roektiningroem (Physics Education Departement Islamic State University Sulthan Thaha Saifuddin Jambi - Indonesia, 2022)
This study aims to determine: (1) the feasibility of students’ worksheet in natural science learning based on POE according to expert lecturers and natural science teachers, (2) students’ science process skill enhancement after using student worksheet in natural science learning based on POE, and (3) students’ responses to student worksheet in natural science learning based on developed POE. This research was a development research with 4D model. The research subject were 11 eighth grade students of Junior High School 2 Pleret. The product trial design used a one-group pretest-posttest design. Data analysis was the conversion of quantitative scores into qualitative values one a scale of four, calculation of percentages, and gain scores. The result showed that: (1) student worksheet in natural science learning based on POE to improve science process skills were declared feasible by expert lecturers and natural science teachers with very good category, (2) mastery of science process skills through observations included good category, while the improving science process skills in terms of pretest-posttest result was in the medium category, and (3) student responses to student worksheet in natural science learning POE was in the very good category.